The Chief Digital Officer – Savior for the Digitalization in German Banks? - Giebe, Carsten (Journal of Economic Development, Environment and People, 2019)
Digitalization is changing processes in the German banking market. This fact means significant challenges for companies. Many German banks could miss the connection in the age of digital transformation. According to a study, the management consultancy McKinsey even expects the return on equity to decline. And if the change that digitalization offers, is not properly implemented. According to the study, German banks are forced to digitalize processes due to low yields, as new players in the market (Fintechs) could shed up to 40 percent of their sales and up to percent of profits. The situation of how to deal with Digitalization correctly is much discussed. Organizationally, a lot was promoted under management aspects, and the industry is talking about the necessity of installing a so called Chief Digital Officer (CDO) next to the Chief Information Officer (CIO) / Head of IT. Is this a valuable solution?